1379. Determination of the Arbekacin Exposure Required to Prevent Amplification of Resistant Subpopulations Using Patient Pharmacokinetics Simulated in a Hollow-Fiber Infection Model (HFIM). (26th November 2018) - VanScoy, Brian D; Lakota, Elizabeth A; Bhavnani, Sujata M; Giesel, Greg; Carranco, Ana I; Nagira, Yu; Ouchi, Shohei; Kondo, Kenichiro; Ambrose, Paul G
Abstract: Background: ME1100 (arbekacin inhalational solution) is an aminoglycoside in clinical development for the treatment of patients with hospital-acquired and ventilator-associated bacterial pneumonia (HABP and VABP, respectively). Due to the increase in resistance of Staphylococcus aureus and Pseudomonas aeruginosa to many antimicrobial agents, it is important to understand the relationships between amplification of drug resistance and each of drug exposure and therapy duration. The objective of the studies described herein was to utilize the HFIM to determine the arbekacin exposure after ME1100 administration required to prevent the emergence of drug-resistant subpopulations. Methods: Duplicate 10-day HFIM assays were completed in which arbekacin total-drug epithelial lining fluid (ELF) concentration–time profiles following inhalational administration of ME1100 every 12 hours were simulated. Four isolates, two methicillin-resistant S. aureus (Arbekacin MIC = 1 mg/L), and two P. aeruginosa (Arbekacin MIC = 4 mg/L), were exposed to total-drug ELF area under the concentration–time curve (AUC) values ranging from 217 to 25, 053 mg hour/L, which were simulated using two different half-lives, 1 hour (α) and 6.93 hours (β). The initial bacterial burden was 1.0 × 10 8 CFU/mL. Samples were collected for enumeration of both the total and drug-resistant bacterial burdens and evaluation of pharmacokinetic samples using LC/MS–MS. Results: Total-drug ELF AUC:MIC ratios required to prevent amplification of MRSA and P. aeruginosa resistance in the HFIM over 10 days were 1, 512 and 2, 942, respectively. The higher AUC:MIC ratio required to prevent resistance for P. aeruginosa was most likely due to the presence of a small colony variant population. The relationship between total-drug ELF AUC:MIC ratio and change in log10 CFU from baseline of the drug-resistant sub-populations found on agar plates on Day 10 took the form of an inverted-U for three pathogens and a step-function for one (Figure 1). Conclusion: These data, which address the goal of considering arbekacin exposures that prevent the development of on-therapy resistance in a clinical setting, will help to provide guidance for future ME1100 dose selection for the treatment of patients with HABP/VABP. Disclosures: B. D. VanScoy, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. E. A. Lakota, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. S. M. Bhavnani, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. G. Giesel, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. A. I. Carranco, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. Y. Nagira, Meiji Seika Pharma Co. Ltd.: Employee, Salary. S. Ouchi, Meiji Seika Pharma Co. Ltd.: Employee, Salary. K. Kondo, Meiji Seika Pharma Co. Ltd.: Employee, Salary. P. G. Ambrose, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support.